Preparation of CaMgSi and Ca7Mg7.25Si14 single phase films and their thermoelectric properties. (19th February 2019) - Uehara, Matsuo; Katagiri, Atsuo; Kurokawa, Mao; Akiyama, Kensuke; Shimizu, Takao; Matsushima, Masaaki; Uchida, Hiroshi; Kimura, Yoshisato; Funakubo, Hiroshi
ABSTRACT: Ca-Mg-Si films were firstly prepared on (001)Al2 O3 substrates by RF-magnetron sputtering method from Mg disc target together with Ca and Si chips. The composition of the deposited films was controlled by adjusting deposition temperature and Ca/Si area ratio of Ca and Si chips on Mg disk target. Ca0.32 Mg0.33 Si0.35 film deposited at 610 K consisted of a single phase of CaMgSi and this CaMgSi phase was stable after heat treated at 770 K under an atmospheric Ar with 5% -H2 . As-deposited film shows the semiconductor behavior and have a power factor of 50 μW/(mK 2 ) at 670 K, while annealed one showed the metallic behavior and its power factor down below 10 μW/(mK 2 ) at 320-770 K. On the other hand, Ca0.27 Mg0. 51 Si0.2 film deposited at 590 K showed no obvious crystalline phase but became single phase of Ca7 Mg7.25 Si14 after heat treatment at 770 K under an atmospheric Ar with 5% -H2 . As deposited film had a large power factor of 100 μW/(mK 2 ) at 670 K. However, power factor decreased below 1 μW/(mK 2 ) at 320-770K after the heat treatment at 770 K under an atmospheric Ar with 5% -H2 .